The Reindustrialization Process – A Strategic Challenge for the Bulgarian Economy - Iliev, Yosif; Shterev, Nikolai; Blagoev, Dimitar (Research Papers, 2015)
A lasting trend towards de-industrialization of the national economy has been formed and deepens in the years of transition in Bulgaria. Some timidly thoughts about strategic issues for reindustrialisation of the national economy have been starting in the last year (resp. 2014) with the beginning of the new programming period of the EU. Political, economic and social realities necessitate new priorities in the economy, especially those that provide accelerated industrial development of Bulgaria.How successful could be such reindustrialisation process in Bulgaria is difficult to be predicted. But it is undisputed that reindustrialisation is extremely complex challenge for the national economy. It is because there are many and complex factors influencing growth, including the internal as well as external ones. And, some of them are unmanageable by their nature.This working paper puts a number of other key issues of reindustrialisation of the national economy. The main accent within the paper is scientific justification for and the resulting progress of the long-term program of reindustrialisation. Thus, the study developed the following key questions: 1.) justify reindustrialisation of the national economy as a long-term process of modernization of the Bulgarian industry; 2) withdrawal some basic aspects of the framework of the Program for reindustrialisation of the national economy; 3) identify mechanisms for determining the priorities of the Programme for reindustrialisation of the national economy; and 4) justification of policies and mechanisms aimed at improving the management of industrial businesses with a view to improving their microeconomic competitiveness.
Keywords: Industrial policy; Reindustrialization; Industrial growth; Microeconomic competitiveness